Estado desenvolvimentista e o Nordeste :o BNB na busca de um modelo de desenvolvimento regional - Cardoso, Gil Célio de Castro (2006)
This research tried to follow up with the way of intervention that a developing State promotes it regional development, once its action departs from a quantitative conception until its acting focused in maintenance, like the strategy of local development input in the Northeastern of Brazil in the 90 s. particularly, the attention was focused onto Banco do Nordeste which, between 1995 and 2002, achieved a organization changing process to get fit itself to the new conception of development and State, that advocates the maintenance and the participation of the society in its accomplishment, becoming itself the main agent of the Federal Government in the Region. By taking over the strategy of local development, Banco do Nordeste starts, at least in speech, to be less of a bank to become more of a development agent , representing some development and hope to overcome the social and economical inequalities of the Region. The hypothesis that surrounds this essay is that this reorientation experienced at Banco do Nordeste is related to three factors: timing; the Institution of a project of international technical cooperation with PNUD; the unrest of an employees group, who used to fight for the acting increase of the Bank to beyond the credit acting; and, above all, the juncture created in Ceara from the second half of the 80 s, expressed, mainly, for the political rise of a group of businessmen, who took over and modernized the standards of public management in the State, transforming the cearense experience into reference in Brazil and the world. The research was developed from information got through the use of semi-structured interviews and documental research and, as complementary resource, field observation. The interviews were done with BNB managers between 1995 and 2003, some of them current administrators (2003-2006), plus one of CAPEF directors and the present president of AFBNB. The research revealed that strategic place taken by BNB in the period studied did not come to represent a rupture in its organizational culture, being strongly attached to factors that allows its operation. When some of these elements stopped existing, it was observed a retracing in the pattern of state intervention in the Region. This conclusion restates the vision of State that guided this thesis, identified as relationships field, of different interests; space where social conflicts are established; incarnated through the institutions